Cultural Tourism - Raj, Razaq (CABI, 2014)
This chapter introduces conceptual, theoreti cal, policy and management dimensions of cul ture and presents various themes and critical discourses that underpin the chapters within this book. With an array of cultural tourism books on the market, this volume is distinctive in its philosophy: the authors link the concep of culture to the notion of identity, both indi vidual and collective. In doing so we recognize the importance of individual, community and national identity formation, through commu nity and national celebrations of culture, through inter-cultural dialogue and engagemen and all of these within the frame of tourism. In some cases, the individual chapter authors illus trate host communities ‘staging’ cultural spec tacles for tourist consumption through events and festivals; in others, we see local communi ties living their daily lives with the consumption of cultural tourism as a by-product; and in others we see the connection with tourism as a tan- gential and sometimes even accidental occur- rence. However, in all instances we see culture and tourism woven together in a cross- pollinating interaction, whereby both the tour- istic and the cultural experience is a richer one for all those involved.